2007
DOI: 10.1109/vetecs.2007.205
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Coverage and Reducing Power Consumption in Peer-to-Peer Networks Through Airborne Relaying

Abstract: Abstract-Over the years peer-to-peer (P2P) multi-hop relays have been studied for mobile ad-hoc networks (MANETs) to overcome poor signal coverage and to improve connectivity. However, for an urban environment, particularly with a sparse mobile distribution, a ground relay is not able to achieve significant benefits, mainly due to the extremely high pathloss and shadowing encountered. Dedicated airborne relay nodes, at a height of hundreds or thousands of meters, can provide much better coverage, and hence imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 7 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…They are also operated as an ad hoc wireless mesh network infrastructure that connects such isolated areas to a communication infrastructure [7][8][9], which could be a promising solution, particularly for collecting sensor data obtained in these areas. The benefits of airborne relaying, in which a UAV provides an interconnection between an isolated area and a communication infrastructure, have been discussed [10]. It was reported that airborne connection provides better con-nectivity and throughput than ground connections because three-dimensional positioning of relaying nodes provides line-of-site (LOS) propagation and suppresses shadowing and fading effects more effectively.…”
Section: Introductionmentioning
confidence: 99%
“…They are also operated as an ad hoc wireless mesh network infrastructure that connects such isolated areas to a communication infrastructure [7][8][9], which could be a promising solution, particularly for collecting sensor data obtained in these areas. The benefits of airborne relaying, in which a UAV provides an interconnection between an isolated area and a communication infrastructure, have been discussed [10]. It was reported that airborne connection provides better con-nectivity and throughput than ground connections because three-dimensional positioning of relaying nodes provides line-of-site (LOS) propagation and suppresses shadowing and fading effects more effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the Line-of-Sight (LoS) characteristics of the flying platform, this kind of airborne relay equipment can provide more coverage or increase the link capacity for heavy loading area. The coverage emulation studied by Feng et al [2] also adopted multi-HAP on signal relay missions. The increment of link capacity was proved by Grace et al [3] and Elshaikh et al [4].…”
Section: Introductionmentioning
confidence: 99%